Digital speech interpolation advantage of statistical time division multiplexer - Shah , Asadullah; Khatri, Krishan Lal (College of Computer Science & Information Systems, Karachi, 2011)
This paper discusses Digital Speech Interpolation (DSI) advantage of Statistical Time Division Multiplexer (STDM) for Random Packet Loss scenarios. In order to harness this advantage each source speech is compressed at 6.4 kbps, Voice Activity Detector (VAD) is used for each source, and packet loss mechanism is introduced to achieve maximum DSI advantage. It is observed that for maximum of 9 users channel capacity, extra 3 users, i.e. total 12 users can be accommodated with 3% speech frame losses, which results in an advantage of 12/9 = 1.33. Keywords: Digital Speech Interpolation (DSI), Statistical Time Division Multiplexing (STDM), Voice Activity Detector (VAD)